2019
DOI: 10.1186/s12879-019-4573-3
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis outbreaks among students in mainland China: a systematic review and meta-analysis

Abstract: BackgroundIn recent years, tuberculosis outbreaks in schools have occurred more frequently in China than in other parts of the world, and have posed a public health threat to students and their families. This systematic review aimed to understand the epidemiological characteristics of tuberculosis (TB) outbreaks and analyze the factors associated with TB outbreaks in schools in China.MethodsWe conducted this systematic review following the standard procedures of the Cochrane Collaboration and the Preferred Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…This difference indicated that TB incidence among students had a more obvious seasonal trend. Additionally, a recent systematic review 29 showed that the index case in about half TB outbreaks in schools occurred in winter, with an average outbreak duration of 4 months. Outbreaks occurred frequently in winter and spring because of long-term contacts in poorly ventilated rooms during cold weather.…”
Section: Discussionmentioning
confidence: 99%
“…This difference indicated that TB incidence among students had a more obvious seasonal trend. Additionally, a recent systematic review 29 showed that the index case in about half TB outbreaks in schools occurred in winter, with an average outbreak duration of 4 months. Outbreaks occurred frequently in winter and spring because of long-term contacts in poorly ventilated rooms during cold weather.…”
Section: Discussionmentioning
confidence: 99%
“…The commonest transmission sites were households ( n = 9), overnight homeless facilities ( n = 8), and local jails ( n = 8)[ 26 ]. According to a review article on school TB outbreaks in China, 41% of the index patients were found in winter (December to February), followed by 28% in spring (March to May)[ 27 ], possibly because the Chinese study focused on school TB outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis (TB) remains a global threat, and its outbreaks have an enormous social impact [1,2]. Laboratory cross-contamination mimicking outbreaks is a significant problem, especially with multidrug-resistant (MDR) TB strains [3,4].…”
Section: Introductionmentioning
confidence: 99%